Penerapan Pasal 1320 Kuh Perdata Terhadap Tanggung Jawab Penjual Dalam Perjanjian Jual Beli Barang Melalui Media Internet - I Komang Mahesa Putra; Ni Luh Mahendrawati; Desak Gde Dwi Arini (Jurnal Analogi Hukum, 2020)
Abstract-This trade activity by utilizing internet media is known as electronic commerce, or abbreviated as e-commerce. Regarding the relevance of existing legislation with the need for regulations in buying and selling transactions through internet media, especially the seller's responsibility. The formulation of the problem in this writing is how the legal protection for the parties in the sale and purchase agreement through the internet media and how the seller's responsibility in the sale and purchase agreement based on article 1320 of the Civil Code. The author uses the type of normative legal research and the problem approach used is the basis of the conceptual approach and legislation. The agreement needed to give birth to an agreement mandated in Article 1320 of the Civil Code is considered to have been reached if the statement of one party was received by the other party. In summary, an agreement is considered to have taken place when one of the parties agreed. The government should provide more stringent supervision for the parties who carry out this electronic transaction, namely by conducting a registration of all activities involving public interest in electronic traffic. Keywords: Sale and Purchase Agreement, Seller responsibilities, e-commerce Abstrak-Kegiatan yang menggunakan elektronik komersil sudah digandrungi beberapa orang dengan penggunaan yang semakin meningkat dengan pesat setiap tahunnya atau disingkat e-commerce. Berkaitan dengan relevansi peraturan perundang–undangan yang sudah ada dengan kebutuhan akan peraturan dalam transaksi jual beli melalui media internet terutama pertanggungjawaban penjual. Rumusan masalah dalam penulisan ini adalah bagaimana perlindungan hukum bagi para pihak dalam perjanjian jual beli melalui media internet dan Bagaimana tanggung jawab penjual dalam perjanjian jual beli barang berdasarkan pasal 1320 KUH Perdata. Penulis menggunakan tipe penelitian hukum normative dan pendekatan masalah yang digunakan adalah dasar pendekatan konseptual dan Peraturan perundang-undangan. Persetujuan antara kedua orang yang menjalin suatu hubungan keperdataan di anggap telah sah apabila keduanya setuju. Ringkasnya, suatu perjanjian dianggap telah terjadi pada saat salah satu pihak menyatakan sepakat. Pemerintah seyogyanya memberikan pengawasan yang lebih ketat lagi bagi para pihak yang melakukan transaksi elektronik ini yaitu dengan jalan melakukan suatu pendaftaran terhadap segala kegiatan yang menyangkut kepentingan umum didalam lalu lintas elektronik. Kata Kunci: Perjanjian jual beli, tanggung jawab penjual, e-commerce